Squint SAR Algorithm for Real-Time SAR Imaging - Sahay, Peeyush; B., Vaidya DhavalKumar; Lokesh Kiran, Kadali (IEEE International Conference on Electronics, Computing and Communication Technologies (Online), 2022)
Conventional squint mode ω-k algorithm requires higher memory and processing time to generate synthetic aperture radar (SAR) images in the case of a large range to scene center, high squint, and large swath. The high memory and processing time requirements make the algorithm the least preferred solution to implement in real-time SAR image generation on multi-core processor hardware. This paper presents various real-time implementation problems associated with conventional squint mode ω-k algorithm implementation. This paper presents a squint ω-k algorithm with a modified time-domain reference function generation approach to mitigate the multi-core processor's processing time and memory requirement problems for real-time SAR image generation. The proposed method is implemented on real-time hardware and validated on real SAR data for 1-meter and 3-meter resolutions.